Pengaruh latihan lari kijang jarak 60 meter terhadap peningkatan kecepatan lari 100 meter pada atlet sprinter atlet atletik PPLP NTB - Nurrahma Aulia; Herman Syah; Ali Imran (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2023)
The problem in this research is the lack of aerobic endurance in NTB PPLP athletes when carrying out observations. This study aims to determine whether or not there is an effect of 60 meter deer running training on 100 meter running speed in PPLP NTB athletic sprinters. In this research, the author examines the 60 meter sprint training and the speed of the 100 meter run. The aim of this research was to determine the effect of 60 meter running and speed training on the 100 meter run. The method used in this research is the experimental method with a two group pretest-posttest research design. In this research the author took a sample of 16 people. The research instrument used is the sprint test. Based on the processing and analysis of data on improvements from the results of the 60 meter deer running test training test, testing the hypothesis using a similar sample t-test, it was obtained that the t-count for the 60 meter deer running training test was 10,40 > t-table 1.895, thus Ho was rejected and Ha was accepted. So this research concluded that: "There is an effect of 60 meter running deer training on increasing 100 meter running speed in PPLP NTB athletic sprinters" while the hypotension test with a similar sample t test obtained a t-calculated speed training value of 13,10 > 1.895. So Ho is rejected and Ha is accepted. So the research concluded that: "There is an influence of 60 meter deer running training on increasing 100 meter running speed in PPLP NTB athletic sprinters."